Low-speed gas knife protection for the large aperture optical component in high-power laser systems - Peng, Ge; Gao, Qiang; Dong, Zhe; Chen, Jiaxuan; Zhang, Peng; Lu, Lihua (Frontiers in Physics, 2023)
In high-power laser systems, fused silica aerosols produced by laser-induced damage to optical components impede further improvement in operation efficiency. To mitigate aerosol threats, low-speed gas knives are an attractive online option. Herein, we investigate the protective mechanism of a low-speed gas knife (<20 m/s) against aerosol invasion on the optical component. First, aerosol particles invaded the surface experimentally in two ways and were detected both in the core and non-core regions, depending on the coverage area of the protection flow. Particle sedimentation percentages can directly reflect the protection capability of the gas knife flow. Since a 'midstream defect' is readily apparent, a CFD model was developed to explain the phenomenon from the perspective of velocity distribution. Additionally, the Euler-Lagrange method was used to track airflow particle motions and reappear the protective process. The numerical and experimental results on protection efficiency are closely correlated. The numerical calculation indicates that the ‘midstream defect' manifested in the core region is possibly attributed to the turbulent dispersion and anisotropic near-wall effects of particles of various diameters, while in the non-core region, the mechanism differs. This work provides a framework for airflow clean designs inside high-power laser systems.